THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE - Moch. Ardiansyah Pramudya; Abdul Khodir Djaelani; Nur Hidayati (International Journal of Cultural and Social Science, 2025)
This study examines the effect of training and work motivation on the performance of Café Nakoa Malang employees, with job satisfaction as a mediating variable. The study population consisted of 103 employees spread across four Café Nakoa branches, all of whom were sampled using saturation sampling techniques. The method used was a survey with data collection through questionnaires, which were then analysed quantitatively using SEM-PLS via the SmartPLS 4 software. The results showed that training and motivation had a positive and significant effect on performance, both directly and through job satisfaction. These findings underscore the importance of effective training and a fair motivation system in enhancing employee satisfaction and performance, particularly in the service industry with a self-service system. The research model was also proven to be valid and reliable, with significant relationships among the main variables.